2004
DOI: 10.1051/vetres:2004013
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the trend of the French BSE epidemic over six birth cohorts through the analysis of abattoir screening in 2001 and 2002

Abstract: - . Logistic regression models were run to compare the prevalence of BSE on successive birth cohorts, using a pair-wise method of controlling for age at testing; the prevalence on the first one, determined on animals slaughtered in 2001, was compared to the prevalence on the following one determined on animals slaughtered in 2002. Five models were performed in order to compare the birth cohorts preceding and following the months of June 1993 (i.e. July 92-June 93 birth cohort compared to July 93-June 94 birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
(21 reference statements)
2
12
0
Order By: Relevance
“…As observed from the abattoir and fallen stock surveillance data, before the strong decrease of the risk that started on the birth cohort 1995-1996, the BSE prevalence was still increasing significantly in the overall French territory between the birth cohorts July 1993 through June 1994 and July 1994 through June 1995 [19]. However, the prevalence was similar for both birth cohorts in western France (3 regions including Brittany) [24].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…As observed from the abattoir and fallen stock surveillance data, before the strong decrease of the risk that started on the birth cohort 1995-1996, the BSE prevalence was still increasing significantly in the overall French territory between the birth cohorts July 1993 through June 1994 and July 1994 through June 1995 [19]. However, the prevalence was similar for both birth cohorts in western France (3 regions including Brittany) [24].…”
Section: Discussionmentioning
confidence: 74%
“…However, the prevalence was similar for both birth cohorts in western France (3 regions including Brittany) [24]. It has been hypothesised [19] that exposure decreased earlier in western France than in any other part of France because feed manufacturers were more aware of the disease in this region. This is likely because the BSE index cases were in western France and the apparent incidence was higher than elsewhere.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, in both the UK and France it has been identified that dairy cows have a risk of BSE approximately three times higher than that of beef cows, once confounding factors such as age at culling or region of origin have been accounted for [33,45,68]. This is simply explained by a higher use of compound feed in dairy farms.…”
Section: Risk Factorsmentioning
confidence: 99%
“…This method was applied to French data [45] and provided evidence of a major decrease of the exposure between birth cohorts 94-95 and 95-96 for slaughtered animals (OR = 0.46, 95% CI 0.27-0.78). If the assumption of a steady surveillance is not fulfilled, the changes in the surveillance must be taken into account, which is possible using an APC model.…”
Section: Evolution Of the Bse Prevalence Over Yearsmentioning
confidence: 99%